2007
DOI: 10.3892/ijmm.19.4.653
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of regucalcin mRNA expression in the hearts of rats administered with free radical compound: The administration-induced death is accelerated in regucalcin transgenic rats

Abstract: Abstract. The expression of regucalcin, a regulatory protein in the intracellular signaling system, in the hearts of rats was investigated. Regucalcin expression was examined using reverse transcription-polymerase chain reaction and Western blot analysis. Regucalcin mRNA and its protein levels in the hearts of male and female rats were significantly decreased with increasing age (50 weeks old) as compared with that of 5-week-old rats. The effect of 1,1-diphenyl-2-picryl-hydrazyl (DPPH), a compound that produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Regucalcin mRNA expression may be altered under various pathophysiological conditions. It was previously demonstrated that regucalcin mRNA and protein levels in the hearts of male and female rats decreased with increasing age, as they were found to be lower in 50-week-old compared to those in 5-week-old rats ( 26 ). The effect of 1,1-diphenyl-2-picrylhydrazyl (DPPH), a compound that produces free radicals, on regucalcin mRNA expression in the hearts of 5-week-old female rats was previously investigated ( 26 ).…”
Section: Expression Of Regucalcin In the Heartmentioning
confidence: 98%
See 1 more Smart Citation
“…Regucalcin mRNA expression may be altered under various pathophysiological conditions. It was previously demonstrated that regucalcin mRNA and protein levels in the hearts of male and female rats decreased with increasing age, as they were found to be lower in 50-week-old compared to those in 5-week-old rats ( 26 ). The effect of 1,1-diphenyl-2-picrylhydrazyl (DPPH), a compound that produces free radicals, on regucalcin mRNA expression in the hearts of 5-week-old female rats was previously investigated ( 26 ).…”
Section: Expression Of Regucalcin In the Heartmentioning
confidence: 98%
“…It was previously demonstrated that regucalcin mRNA and protein levels in the hearts of male and female rats decreased with increasing age, as they were found to be lower in 50-week-old compared to those in 5-week-old rats ( 26 ). The effect of 1,1-diphenyl-2-picrylhydrazyl (DPPH), a compound that produces free radicals, on regucalcin mRNA expression in the hearts of 5-week-old female rats was previously investigated ( 26 ). Heart regucalcin mRNA levels were found to be reduced at 60 or 180 min following a single intraperitoneal administration of DPPH (5 mg/kg body weight), suggesting that free radical stress exerts a suppressive effect on gene expression.…”
Section: Expression Of Regucalcin In the Heartmentioning
confidence: 98%